Taking Stock of Suffragists: Personal Reflections on Feminist Appraisals - Strong-Boag, Veronica (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2010)
Standpoint theory has made today’s feminist historians especially conscious of the ‘situatedness’ of all approaches. The intimate relationship of scholars with their human subjects means that choices and interpretations readily become sites of engagement in modern contests of principles and practice. Because the franchise campaigns were a leitmotif of the first women’s movement, suffragists have a particular purchase on the feminist imagination. This special significance makes appraisals of Canadian activists an important test of scholarly and popular standpoints in the construction of a meaningful past. This paper sets forth one feminist historian’s reflections on engagement with the suffragists.